Acetabular Component and Liner Selection for the Prevention of Dislocation After Primary Total Hip Arthroplasty. Issue 12 (December 2021) - Kunze, Kyle N.; Premkumar, Ajay; Bovonratwet, Patawut; Sculco, Peter K.
Abstract : Primary total hip arthroplasty (THA) is a reproducible and efficacious procedure for patients with end-stage osteoarthritis; however, dislocation remains the most common cause of revision arthroplasty. Technological advancements in acetabular component design and liner options, in conjunction with a more comprehensive understanding of the spinopelvic factors that influence dislocation, will likely reduce the risk of dislocation and revision over time. The contemporary liner and shell options for primary THA, in order of increasing constraint and stability, include (1) neutral, (2) lateralized, (3) face-changing (oblique), (4) lipped (high-wall) with or without lateralization, (5) modular and anatomic dual-mobility, and (6) constrained options. Different liner designs can alter functional anteversion, inclination, and jump distance, and can be used to minimize a single predictable dislocation vector (lipped [high-wall] liners) or multiple vectors of instability risk when the dislocation direction is unpredictable (dual-mobility liners). Liner selection should be based on the patient-specific risk of dislocation, including static anatomic (e.g., large anterior inferior iliac spine or greater trochanter morphology), dynamic anatomic (e.g., limited sitting-standing change in the sacral slope), and demographic or medical (e.g., neurocognitive disorders and obesity) risk factors.